Efficacy and safety of JMT103 in patients with unresectable or surgically-challenging giant cell tumor of bone: a multicenter, phase Ib/II study - Hairong Xu; Yong Zhou; Li Liang; Jingnan Shen; Wangjun Yan; Jin Wang; Jianmin Li; Xiaojing Zhang; Gang Huang; Wenzhi Bi; Zheng Guo; Yanbin Xiao; et al. (Nature Communications)
Abstract This was a multicenter, single-arm, open-label, phase Ib/II study (NCT04255576), aimed to evaluate the efficacy and safety of JMT103 in patients with unresectable or surgically-challenging giant cell tumor of bone (GCTB). JMT103 (2 mg/kg) was administered subcutaneously every four weeks, with loading doses on days 8 and 15. The primary endpoint was the objective tumor response rate (OTR) based on best response, defined as the proportion of patients who achieved elimination of at least 90% of the giant cells or radiologic complete or partial response per the modified Inverse Choi density/size (mICDS) or modified European Organization for Research and Treatment of Cancer (mEORTC) within 12 weeks. Secondary endpoints included objective response rate (ORR) per mICDS and mEORTC, and safety. A total of 139 patients were enrolled, and 135 were analyzed for efficacy. OTR, determined by the independent review committee (IRC) was 93.3% (95% CI 87.7-96.9). Treatment-related adverse events occurred in 90 (64.7%) patients, with hypophosphatemia and hypocalcemia being the most common. No serious treatment-related adverse events were observed. Thus, JMT103 demonstrates potential as a therapeutic option for GCTB.